Comparison of chest compression injuries during CPR between the 2010 and 2005 AHA guidelines in autopsy cases in Chiang Mai, Thailand - Amornlertwatna, Yutti; Narongchai, Paitoon (Biomedical Sciences and Clinical Medicine, 2016)
Background The 2010 American Heart Association (AHA) Guidelines for Cardiopulmonary Resuscitation (CPR) and Emergency Cardiovascular Care (ECC) focus more on the importance of chest compressions than the 2005 AHA Guidelines. Observations show that injuries from CPR under the 2010 guidelines are more serious than those that occur under the 2005 guidelines. This may be a contributing factor in the death of these patients. Objective To study and compare injuries from CPR chest compressions under the 2010 AHA Guidelines with those that occurred under the 2005 Guidelines. Material and methods Retrospective, prospective and descriptive studies were performed on 254 deceased persons who had received chest compressions under the 2005 or 2010 AHA Guidelines. Results This study found a higher incidence of injuries from cases of chest compression (2010 guidelines) than in the controls (2005 guidelines). Injuries that were statistically significant (p<0.05) included: skin contusion/abrasion, intercostal muscle contusion, sternal fracture, rib fracture, pericardial contusion, pericardial rupture, hilar and heart contusion, cardiac contusion, and spleen rupture. Conclusion Injuries found from CPR chest compressions, which followed the 2010 AHA guidelines, were statistically greater in quantity and severity than those found in persons following the 2005 guidelines. Chronic liver diseases, such as cirrhosis and fatty liver disease, can cause increased injury from CPR chest compressions.